The Great Kettles : a tale of time - Morrissey, Dean (H.N. Abrams, 1997)
Hoping to visit the friend he had to leave behind when his family moved, Joey builds a time machine and makes an eventful trip to the land where Father Time, Mother Nature, the Man in the Moon, and other such characters life.